OBESITY, LEFT VENTRICULAR REMODELING, AND 24-HOUR BLOOD PRESSURE PROFILE IN MILITARY PERSONNEL WITH ARTERIAL HYPERTENSION: A CONTEMPORARY CLINICAL ASSESSMENT - Salikhov B.R; Alyavi A.L (TADQIQOTLAR, 2025)
Abstract Background. Obesity is a major modifiable risk factor for cardiovascular disease and strongly contributes to the development of hypertension and left ventricular (LV) remodeling.  Military  personnel  represent  a  unique  population  with  high cardiometabolic risk due to occupational stress and lifestyle patterns. Objective. To investigate the relationship between body mass index (BMI), LV structural  remodeling,  and  circadian  blood  pressure  (BP)  profile  in  hypertensive servicemen.